Product innovation and product innovation marketing: theory and microeconometric evidence - Ulrich Kaiser (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper derives a three stage Cournot?oligopoly game for product innovation, expenditure on introducing the product and competition on the product market. Product innovation is assumed to increase consumer utility but is effective only if the innovating firm invests in marketing, so that consumers become aware of the newly developed product. Firms first decide whether or not to conduct product innovation and then determine their expenditure for bringing the new product to the market. In the final stage of the game, they are involved in competition on the product market. Key findings of the theoretical model are that both the marketing of a product innovation and a firm?s propensity to introduce an innovation decrease with an increase in the number of competitors and the degree of product substitutability. An increase in market demand has a positive effect on product innovation and marketing effort. These findings are tested empirically using survey data from 519 German service sector firms which mainly produce consumer goods. A simultaneous sequential Tobit model is applied in the empirical part of this paper. It turns out that the predictions of the theoretical model are supported by the empirical findings.
Keywords: C34; L2; 330; econometric models; game theory; new product research; Innovationswettbewerb; Oligopol; Marketing; Spieltheorie; Industrieökonomik; Schätzung; Dienstleistungssektor; Theorie; Deutschland